Utilização de um secador solar para desintoxicação da torta de mamona - Anunciação, Elenise Barreto Barbosa da (2007)
It´s been motivating motivated by the current rulers as an energy solution the use of the biodiesel as source of energy, that doesn't damage the environment and promotes the development of the areas where the base plant are grown. The process of production of the biodiesel, starting from the castor oil plant and its derivers, generates a known product as castor oil plant pie that has been used as fertilizer. Once disintoxicated, it can serve as animal ration, because it contains high content of proteins, presenting larger joined value. The disintoxication process, can be obtained through the process of drying the pie with the construction and use of models of dryers capable to elevate the temperature of the castor oil plant pie to approximately 60ºC.In this temperature the product tends to eliminate the ricina, with the aid of an aqueous solution of hydroxide of calcium, or still reach higher temperatures to make the disintoxication without a chemical treatment. It was made a bibliographical research about known processes of disintoxication of the castor oil plant pie from the autoclave use to the drying direct exposure to the sun. Starting from the state of the art and identification of the object, it was chosen solar dryers to eliminate the ricina. It was applied two types of solar dryers: the one of solar direct exposure, and the one with concentrador. The castor oil plant pie was separated in samples, with measurement of its initial mass, codified and placed in the dryers. The results were presented in graphs and tables forms, with the values of temperatures noticed. It was noticed the variations of temperature and the relationships analyzed related with the ricina content eliminated from the pie. The analysis of the ricina content was accomplished by Embrapa - Campina Grande, by eletroforese method. The analysis of the result of considering the content of ricina of the samples. It was observed that, we obtained lower rate of ricina in samples that had larger drying time and average value temperature above 60ºC. Comparing with the ones submitted to higher temperatures and in a shorter period of time. It was possible to evaluate the efficiency of the dryers in the desintoxication process of the samples, as well as the type of more appropriate dryer for the drying pie process. Finally, it was concluded that the solar dryer with concentrador presents higher values temperatures than the direct exposure one. So, it´s being more opportune applied in the castor oil plant pie drying process. However, more than one hour for drying time is needed